Incentives, Social Norms, and Business Cycle: An Example of Business Loans Provision by Islamic Banks - M. Ishaq Bhatti; Suren Basov (Bank Indonesia, 2022)
The interaction of social norms and incentives is a subject of growing interest in economic literature. Basov and Bhatti (2013) pointed out that invoking a social norm is both a blessing, since it allows mitigating moral hazard problem, and a curse, since it restricts the class of admissible contractual arrangements. In this paper, we reiterate this point using particular example of the effects of restrictions imposed on contracts by Shariah law on the optimal risk-incentive trade-off. We show that extra rigidity imposed by Shariah law leads to a greater reluctance to invest into daring new ideas, which are profitable in expectation, but may also result in significant losses. A shared set of social norms between the lender and the entrepreneur allows mitigating adverse consequences of the excess rigidity through creation of good will and may even lead to an improved performance. The adverse consequences may vary according to the stages of business cycle. As a result, recessions can have negative long-term effects and longer booms may be followed by longer recessions. We also hypothesize that turning a social norm into a law will deprive it of the ability to generate good will, while leaving the negative aspects intact. We find a tentative support of this hypothesis by comparing relative performance of Islamic banks in three regions: South East Asia (primarily, Malaysia), Middle East, and the UK.